Pilot Evaluation of Field Pea Accessions Under Water Deficit Conditions - Grace B. Vinarao; Krishna Ghimire; Donna K. Harris (International Journal of Plant Biology)
Field pea, a key pulse crop for sustainable agriculture, faces significant production challenges due to drought, exacerbated by extreme climatic changes. This study evaluated 17 field pea plant introductions (PIs) and two commercial varieties under greenhouse conditions to assess their performance, determine the relationships between agronomic traits and grain yield (GY), and identify genotypes with stable yields under drought stress. Two water treatments were applied: 100% field capacity for well-watered (WW) and 60% field capacity for water deficit (WD) conditions, with drought stress imposed 21 days after planting. Significant genotypic variation was observed under both conditions. Water deficit significantly reduced GY, the number of pods per plant (NPP), plant height (PH), aboveground dry vegetative biomass (ADVB), and days to maturity (DTM) while increasing stomatal density on both adaxial (SD.ADX) and abaxial leaf surfaces (SD.ABX). Traits associated with GY in WW, such as NPP, PH, ADVB, and SD.ADX, showed stronger correlations under WD, with DTM being significantly associated with GY only in WD. Top-performing genotypes in both conditions exhibited higher pod numbers, increased aboveground dry vegetative biomass, late maturity, and lower adaxial stomatal density. Notably, PI 272215 was identified as a top performer under both conditions, with an 88% yield stability index. PI 180702 demonstrated comparable performance to PI 272215 but with no yield loss under the same conditions. These findings can be used for future field pea breeding programs aimed at developing drought-tolerant field pea varieties.